(untitled) (European Journal of Pure and Applied Mathematics, 2018)
In this research article, we study some properties of doubt bipolar fuzzy H-ideals in BCK/ BCI-algebras. Doubt bipolar fuzzy H-ideals are connected with doubt bipolar fuzzy subalgebras and doubt bipolar fuzzy ideals. Moreover, doubt bipolar fuzzy H-ideals are characterized using doubt positive t-level cut set, doubt negative s-level cut set and H-Artin BCK/BCI-algebras.